Pembelajaran E-learning Berbasis Edmodo: Studi Kasus di SD Negeri 106 Pekanbaru - Fitria Fitria (Bedelau: Journal of Education and Learning, 2020)
This research was carried out in the background by the presence of the corana outbreak virus so as to cease the activity of teaching and learning process carried out at home. Where teachers must continue to provide lessons to students, for that teachers do the e-learning method based on Edmodo. Online-based learning can help teachers and students to continue to do the teaching process, in the platform the teacher can upload subject matter and assignments will be done by students, besides teachers and students can also carry out discussions in the form provided. This research instrument used observation sheets and conducted 4 meetings. The purpose of this study was to determine edmodo-based e-learning learning. Based on the results of observations and data analysis, it can be concluded that e-learning learning can help teachers and students in the teaching process.